Comparing diel activity patterns of wildlife across latitudes and seasons: Time transformations using day length. Issue 12 (20th September 2019) - Vazquez, Carmen; Rowcliffe, J. Marcus; Spoelstra, Kamiel; Jansen, Patrick A.
Abstract: Camera trapping allows scientists to study activity patterns of animals under natural conditions. However, comparisons of activity patterns across seasons or latitudes can be biased, because activity is often attuned to sunrise and sunset, the timing of which varies with latitude and season. Existing transformation methods to solve this problem have limitations. Here, we explore whether and how activity patterns can be transformed more accurately using two alternative 'double anchoring' transformations – equinoctial and average anchoring – that anchor activity time to two chosen anchor points during the study period. Using simulated noisy datasets mimicking species with either crepuscular, diurnal or cathemeral activity patterns, we compared the ability of different transformation methods to extract the latent pattern and activity levels under different study conditions. We found that average anchoring best retrieved the original diel activity pattern and yielded accurate estimates of activity level. Two alternative transformation methods – single anchoring and equinoctial anchoring – performed less well. Bias in estimates from using untransformed clock times was most marked (up to 2.5‐fold overestimation) for longer studies covering 4–5 months either side of an equinox at high latitude, and focusing on crepuscular species. We applied the average anchoring method to 9 months of data on Red deer Cervus elaphus, Wild boar Sus scrofa and Mouflon Ovis amon musimon activity as captured by camera traps in National Park Hoge Veluwe, the Netherlands. Average anchoring revealed more pronounced peaks of activity after sunset than was apparent from untransformed data in red deer and wild boar, but not for mouflon, a cathemeral species. Similarly, activity level was lower when calculated using average anchored time for red deer and wild boar, but no difference was observed for mouflon. We conclude that transformation of time might not be necessary at latitudes below 20°, or in studies with a duration of less than a month (below 40° latitude). For longer study periods and/or higher latitudes, average anchoring resolves the problem of variable day length. Code is provided. The transformation functions are incorporated in the r ‐package 'activity '.